Development of the Emergency Department Senior Abuse Identification (ED Senior AID) tool. Issue 4 (8th August 2018) - Platts-Mills, Timothy F.; Dayaa, Joseph A.; Reeve, Bryce B.; Krajick, Kayla; Mosqueda, Laura; Haukoos, Jason S.; Patel, Mehul D.; Mulford, Carrie F.; McLean, Samuel A.; Sloane, Phil D.; Travers, Debbie; Zimmerman, Sheryl
ABSTRACT: Emergency departments (EDs) are an important health care setting for the identification of elder abuse (EA). Our objective was to develop an ED-based tool to identify EA. The initial tool included a brief cognitive assessment, questions to detect multiple domains of EA, and a physical examination. Refinement of the tool was based on input from clinical experts and nurse and patient feedback. The revised tool, which included 15 questions about EA, was then tested in an academic ED. We calculated the inter-rater reliability, sensitivity, and specificity of individual EA questions. Among ED patients age≥65 ( N  = 259), 17 (7%) screened positive for suspicion of EA. We identified a combination of six questions that cover the included domains of EA, demonstrated good or excellent inter-rater reliability, and had a sensitivity and specificity of 94% (95% confidence interval (CI) 71–100%) and 90% (95% CI 85–93%), respectively. These results inform a proposed screening tool for multisite validation testing.